Reassessing Brer Rabbit: friendship, altruism, and community in the folklore of enslaved African-Americans. - Lussana, Sergio (Slavery & Abolition, 2018)
This article examines the Brer Rabbit trickster tales of enslaved African Americans. It challenges earlier interpretations of scholars who view the world of Brer Rabbit as amoral and anarchic. Lawrence Levine, for example, claimed that friendship was portrayed as a ‘fragile reed’ in the Brer Rabbit tales. Instead, this article argues that Brer Rabbit did not live in an amoral world; rather, he lived in a world of ethical boundaries. Indeed, friendship, altruism, and commitment to vulnerable members of the community were prized – not derided. For enslaved people in the United States, these values were crucial for survival; yet historians have failed to pay sufficient attention to these themes in the tales.